PENGARUH TENAGA KERJA EKONOMI KREATIF DAN EKSPOR PRODUK EKONOMI KREATIF TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Diba Nur Rahman; Zuhrinal M Nawawi; Annio Indah Lestari (Studia Economica : Jurnal Ekonomi Islam, 2021)
Economic growth is a condition in which a country experiences an increase in gross domestic product (GDP). In this case, exports and employment are things that can affect economic growth. This study aims to analyze the effect of creative labor and exports of creative economy products on Indonesia's economic growth. This research was conducted in Indonesia. The variable is Indonesia's economic growth, the independent variables are creative economy workers and exports of creative economy products. The data used is secondary data. Secondary data were obtained from the yearbook and the official website of the Indonesian Central Statistics Agency and the Creative Economy Agency. The analysis tool used is multiple linear regression with the help of the Eviews 8 program. The results show that all independent variables have a significant effect on Indonesia's economic growth. The value of the coefficient of determination (R square) is 0.815076, which means that Indonesia's economic growth can be explained by the variable factor of creative economy labor and creative economy product exports of 81.5%. While the remaining 18.5% of Indonesia's economic growth is explained by other variables that are not included in the analysis model in this study.